The Mughal Empire under Shah Jahan in Indian History: A Study: A Golden Era of Stability, Art, and Architectural Marvels in the Mughal Empire under Emperor Shah Jahan (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Emperor Shah Jahan (1592-1666) was one of India's largest Mughal emperors. He governed an Empire which was one of the greatest in the world's history. This included Afghanistan, Pakistan, Iran, India, Nepal, Bhutan and Bangladesh today. The scale of the colossal Roman Empire and British Empire was quickly compared. Emperor Shah Jahan's reign was one of India's most stable, successful and democratic periods. In the world of art and design there were unprecedented innovations. During emperor Shah Jahan's rule, the Pacific Throne, the Taj Mahal, the Agra Fort, and many other objects that hold people fascinated even today were created. During this time financial collections rose to the maximum volume. During Emperor Shah Jahan's rule there were no significant rebellions or political invasions.